Exploring the Food Beliefs and Eating Behavior of Successful and Unsuccessful 'Weight Losers' Belonging to Different Areas of Karachi - Shafique, Kausar; Almeida , Margaret (Nurture, 2009)
The objectives of this study was to explore the food beliefs and eating behavior of successful and unsuccessful 'weight losers'; and to find out the nutritional adequacy of food groups, through a 24 hour food recall. A total of sixty participants were selected from 75 respondents on the basis of their past weight loss, and separated into two groups of thirty each; namely successful and unsuccessful 'weight losers'. Data about their food beliefs and eating behaviors were collected through a questionnaire. A 24 hour food recall was also taken. Results showed that both groups of 'weight losers', differed in their food beliefs, eating behavior and energy intake. 'weight losers' of both groups had an inadequate consumption of vegetables, fruits and milk.